Consensus guidelines for the management of brain stem and diffuse midline glioma for low- and middle-income countries - Hafiza Fatima Aziz; Naureen Mushtaq; Fatima Suleman; Asim Hafiz; Mohammad Hamza Bajwa; Ahmed Gilani; Kaynat Siddiqui; Altaf Ali Laghari; Muhammad Usman Khalid; Saqib Kamran Bakhshi; et al. (Journal of the Pakistan Medical Association, 2024)
The understanding of brainstem gliomas and diffuse midline gliomas has significantly increased in the last decade. However, the management paradigm remains a dilemma. The critical location is the foremost factor dictating the outcome. Recent advancements in the field of neuro-oncology are pushing the boundaries of optimal care in the developed world nevertheless, the strategies in low- and middle-income countries (LMICs) need to be tailored according to the resources to improve outcome. The objective of these guidelines is to provide an algorithm-based management plan to cater challenges for healthcare providers in LMICs. Keywords: Algorithms, brain stem, glioma.